Perceptions, cartographies, and ‘cartographies of time’ in the political novel [version 1; peer review: 1 approved, 2 approved with reservations] - Tomasz Mizerkiewicz (Open Research Europe, 2025)
The paper examines the relation of the form of political novel to perceptions. Three possibilities are analysed. First, when the political novel shares perceptions of the hegemonic power. Second, when the novel trains how to suspiciously and critically reveal hegemonic manipulations of perceptions. Third, where the form of the novel enhances and emancipates perceptive faculties of readers and allows them to project new democratic activities. This three-fold relation is also referred to cartographic activities (including cartographies of time) as depicted in political novels.